A 26-year-old female with faulty existing restorations (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
This article has no abstract. The first 100 words appear below:A 26-year-old female came with unaesthetic restorations on the upper four anterior teeth. She gave a history of the restoration of the teeth 6 months ago that underwent progressive marginal discoloration. On clinical examination, two upper central and two lateral incisor teeth were restored by Glass Ionomer cement and Secondary caries were present beneath restorations. Teeth were vital and did not respond to percussion and mobility test. Radiographic examination revealed that the four maxillary anterior teeth (2 central and 2 laterals) had the existing restoration which showed a radioopaque area in the proximal surface but radiolucent areas were also seen beneath the radioopaque area that extends to the dentin.